2B and 3C Proteins of Senecavirus A Antagonize the Antiviral Activity of DDX21 via the Caspase-Dependent Degradation of DDX21 - Zhao, Kuan; Guo, Xiao-Ran; Liu, Shuai-Feng; Liu, Xiao-Na; Han, Ying; Wang, Lu-Lu; Lei, Bai-Shi; Zhang, Wu-Chao; Li, Li-Min; Yuan, Wan-Zhe (Frontiers in Immunology, 2022)
Senecavirus A (SVA), also known as Seneca Valley virus, is a recently emerged picornavirus that can cause swine vesicular disease, posing a great threat to the global swine industry. It can replicate efficiently in cells, but the molecular mechanism remains poorly understood. This study determined the host's different expressed proteins (DEPs) during SVA infection using dimethyl-labeling based on quantitative proteomics. Among the DE proteins, DDX21, a member of the DEAD (Asp-Glu-Ala-Asp)-box RNA helicases (DDXs) family, was down-regulated and demonstrated inhibiting SVA replication by overexpression and knockdown experiment. To antagonize this antiviral effect of the DDX21, SVA infection induces the degradation of DDX21 by 2B and 3C protein. The Co-IP results showed that 2B and 3C did not interact with DDX21, suggesting the degradation of DDX21 did not depend on their interaction. Moreover, the 3C protein protease activity was necessary for the degradation of DDX21. Furthermore, our study revealed that the degradation of DDX21 by 2B and 3C protein of SVA was achieved through the caspase pathway. These findings suggested that DDX21 was an effective antiviral factor for suppressing SVA infection and SVA antagonized its antiviral effect by degrading DDX21, which will be useful to guide further studies into the mechanism of mutual regulation between SVA and the host.